Price stability versus low inflation in Germany: An analysis of costs and benefits - Karl-Heinz Tödter; Gerhard Ziebarth (Deutsche Bundesbank, 1997)
This study empirically investigates for the case of Germany the following question, recently posed by Feldstein (1996): "lf the true and fully anticipated rate of inflation has stabilized at a low level, i.e. two per cent, is the gain from reducing inflation to zero worth the sacrifice in output and employment that would be required to achieve it?" ...
Keywords: 330; Inflationsbekämpfung; Kosten-Nutzen-Analyse; Wohlfahrtsanalyse; Deutschland